Emotional Maturity, Religious Tolerance and Religiosity Within Millennial Generation - Sukmawati, Fitri; Baroroh, Ema Zati; Juwita, Nindya; Amalia, Kiki; Sawani, Yussri (Al-Albab, 2024)
Indonesia’s diversity may be challenging as it can be a double-edged knife in the context of social interaction. Not only supporting positive development direction, the diversity also carries negative influence that may cause inharmony to Indonesian society. In the context of the millennial generation as the future leader, the diversity is also very important for further discussion in response to the efforts of building a harmonious society. Projecting the case study of millennial generation in Pontianak City of West Borneo, this work aims to explore the level of emotional maturity, religiosity and religious tolerance, as well as to verify the relationship between emotional maturity, religiosity and religious tolerance. It is based on a quantitative approach with a type of causality research project. There were 182 samples in this study. The research results show that the Pontianak City millennial generation is in a high category in terms of emotional maturity, religiosity and religious tolerance. Further, the results have proven that emotional maturity and religiosity have a relationship with religious tolerance, which indicates that each dimension of emotional maturity and religiosity has a relationship with religious tolerance. The findings also show that an additional factor that shapes emotional maturity, religiosity and religious tolerance is the educational level of the millennial generation. This indicates that the higher the level of education of the millennial generation, the higher their emotional maturity, religiosity and religious tolerance.